Differential Effects of Light Spectra on Sleep Architecture and Melatonin in Rats - Yuan-Chun Chiu; Pei-Lu Yi; Fang-Chia Chang (Brain Sciences)
Artificial light exposure, particularly from blue-rich sources, has raised concerns about its impact on sleep and circadian rhythms. While blue light’s effects are well-documented, the comparative impact of longer wavelengths, such as orange light (590–635 nm), remains underexplored. This study investigated the effects of 8 h blue (470–490 nm) and orange light exposures (500 lux) on sleep architecture in the next consecutive three days in Sprague-Dawley rats during the light or dark phase of a 12:12 h light–dark cycle. Sleep–wake states were assessed via electroencephalography (EEG) over 72 h. Blue light during the light period suppressed rapid eye movement (REM) sleep acutely and enhanced non-NREM sleep on Days 2 and 3. Orange light during the light period induced no immediate changes but increased NREM sleep on Day 2 with a biphasic REM response—suppression followed by rebound—persisting into Day 3. Blue light during the dark period increased NREM sleep during exposure, followed by suppression in the subsequent light period, with effects normalizing by Day 2. Blue light exposure suppressed melatonin levels compared to controls. These findings highlight spectral and temporal influences on sleep, with blue light exerting stronger acute effects and orange light eliciting delayed, biphasic responses. The results suggest implications for managing light exposure to mitigate sleep disruptions in modern environments.